The THE EFFECT OF PROACTIVE PERSONALITY ON EMPLOYEE PERFORMANCE MEDIATED BY INDIVIDUAL CREATIVITY - Ramdani, Muhammad Rozi; Muhdiyanto, Muhdiyanto (Innovation, Technology, and Entrepreneurship Journal, 2026)
This study aims to analyze the influence of Proactive Personality on Employee Performance with Individual Creativity as a mediating variable. This study uses a quantitative method with the Structural Equation Modeling–Partial Least Squares (SEM-PLS) approach. Data were collected through distributing questionnaires to 108 employees of MSMEs in the Creative Economy sector in Magelang City, using a purposive sampling technique. The results showed that Proactive Personality had a positive and significant effect on employee performance. In addition, Individual Creativity had a positive and significant effect on employee performance. However, Proactive Personality had no effect on Individual Creativity. Mediatively, Individual Creativity was not proven to mediate the influence of Proactive Personality on employee performance. These findings demonstrate the importance of developing individual employee creativity in strengthening the influence of authentic leadership on improving employee performance in the MSME Creative Economy sector.